2020
DOI: 10.3390/nano10122362
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Oxidation of Magnetic and Electrically Conductive Solid-Solution Iron-Rhodium Nanoparticles Synthesized by Laser Ablation in Liquids

Abstract: This study focuses on the synthesis of FeRh nanoparticles via pulsed laser ablation in liquid and on controlling the oxidation of the synthesized nanoparticles. Formation of monomodal γ-FeRh nanoparticles was confirmed by transmission electron microscopy (TEM) and their composition confirmed by atom probe tomography (APT). For these particles, three major contributors to oxidation were analysed: (1) dissolved oxygen in the organic solvents, (2) the bound oxygen in the solvent and (3) oxygen in the atmosphere a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…Note that for PLAL of elements with higher oxygen affinity, such as iron, acetone degassing may be required to minimize the oxidation, and that nanoparticle size dependence of the oxidation degree cannot be excluded. Recently, the role of excluding oxygen during PLAL of FeRh in acetone was investigated in detail by systematically excluding the residual water, the dissolved molecular oxygen, and the bound oxygen in the solvent . When argon or an N 2 /H 2 mixture was used as an atmosphere during PLAL in acetone, the detected oxygen was reduced to 9.8 and 6.9 atom %, and an effect of the bound oxygen by replacing acetone with acetonitrile could not be observed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that for PLAL of elements with higher oxygen affinity, such as iron, acetone degassing may be required to minimize the oxidation, and that nanoparticle size dependence of the oxidation degree cannot be excluded. Recently, the role of excluding oxygen during PLAL of FeRh in acetone was investigated in detail by systematically excluding the residual water, the dissolved molecular oxygen, and the bound oxygen in the solvent . When argon or an N 2 /H 2 mixture was used as an atmosphere during PLAL in acetone, the detected oxygen was reduced to 9.8 and 6.9 atom %, and an effect of the bound oxygen by replacing acetone with acetonitrile could not be observed.…”
Section: Methodsmentioning
confidence: 99%
“…Atom probe tomography revealed 9.6 atom % oxygen in the smaller nanoparticles and no detectable oxygen inside the bigger nanoparticles. Hence, according to the literature, for PLAL of Cu, acetone PLAL under sealed conditions may be enough to suppress the oxidation below detection limit, but in general, oxidation cannot be fully excluded even after solvent drying and degassing with reducing gases, ,, in particular for elements with high oxygen affinity.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of Co carbide nanoparticles was observed by Zhang et al during the nanosecond-pulsed laser ablation of cobalt in acetone [45]. More recently, Nadarajah et al systematically investigated the suppression of nanoparticle oxidation in both acetone, which contains oxygen in its molecular structure, and acetonitrile, which is an oxygen-free molecule, by degassing and drying the organic solvents [17]. They found that independent of the solvent, a combination of both solvent purification methods leads to oxidationminimized Fe-Rh nanoparticles, proven even by atom probe tomography, and no impact of the bound oxygen in the molecule of the organic solvent could be found.…”
Section: Variation Of the Initial Mixing State Of The Target And The Laser Pulse Durationmentioning
confidence: 99%
“…In LSC, a laser beam of high intensity ablates the surface of a bulk material covered by a liquid layer, generating thus nanoparticles that disperse in the liquid. LSC enabled the synthesis of colloidal particles of various alloys, for example, brass [12], bronze [13], Ag-Cu [14], Au-Ag [15], Co-Pt [16], Fe-Rh [17], Ir-Pt [18], Ni-Pd [19], Pd-Pt [20], Pd-Y [21], and Co-Fe-Cr-Mn-Ni [22], by ablation of the corresponding bulk alloys.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Reports on the synthesis of FeNi nanoparticles and strand formation of magnetic nanoparticles can be found in the literature [ 3 , 30 , 42 ]. The strand formation was also demonstrated for further material systems, such as Fe 3 O 4 [ 48 ], Co 3 C [ 43 ], Ni [ 49 , 50 ], FePt [ 42 ], FeCo [ 42 ], FeAu [ 51 ], and FeRh [ 52 ]. However, to the best of our knowledge, a detailed study on the formation of strands using laser-generated size-controlled nanoparticles in a polymer matrix and predicting the formation by simulations is yet to be performed.…”
Section: Introductionmentioning
confidence: 99%